Comment on "Eppur si Muove: Proton Diffusion in Halide Perovskite Single Crystals": Eppur Non si Muove: A Critical Evaluation of Proton Diffusion in Halide Perovskite Single Crystals. Issue 35 (26th July 2021) - Buffeteau, Thierry; Hirsch, Lionel; Bassani, Dario M.
Abstract: A recent report by Cahen and co‐workers is examined that finds the diffusion constant for proton migration in methylammonium lead triiodide single crystals to be 2 × 10 5 ‐fold greater than that previously reported by Sadhu et al. By comparing the conversion of single crystals versus microcrystalline samples, it is concluded that proton diffusion in macroscopic single crystals is accelerated by the presence of defects acting as high‐diffusivity paths. Abstract : The >10 5 discrepancy between recent reports of proton diffusion constants in halide perovskites is analyzed and it is found that the lower value is likely correct. The higher diffusion rate determined from single crystals may be the result of high‐diffusivity pathways.